2016
DOI: 10.14366/usg.15063
|View full text |Cite
|
Sign up to set email alerts
|

Signet-ring cell carcinoma of the appendix: a case report with an emphasis on sonographic findings

Abstract: In this report, we present a rare case of primary signet-ring cell carcinoma of the appendix in a 51-year-old woman with right lower quadrant pain. Since non-specific concentric appendiceal wall thickening was found in a radiologic evaluation, it was misdiagnosed as non-tumorous appendicitis. An in-depth examination of the correlation between sonographic and histopathologic findings demonstrated that a single markedly thickened hypoechoic layer was well correlated with the diffuse infiltration of tumor cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Thirdly, the thickness of the appendix wall is significantly higher than that of the fat infiltration around the appendix. [22]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirdly, the thickness of the appendix wall is significantly higher than that of the fat infiltration around the appendix. [22]…”
Section: Discussionmentioning
confidence: 99%
“…The pathological examination found that the appendix wall was asymmetrically thickened due to signet ring cell infiltration, and the patient underwent right hemicolectomy. [22]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the current case samples, one case has been reported in a case report that described the sonographic findings of signet-ring cell carcinoma (Case 7) in the appendix. [ 11 ]…”
Section: Ase R Eportmentioning
confidence: 99%